Total synthesis of (−)-himalensine A and development of novel C(sp3)-H functionalisation reactions - Shi, H (2018)
This thesis describes the 22-step enantioselective total synthesis of (-)-himalensine A, and the Cp*RhIII catalysed amidation of unactivated C(sp3)-H bonds utilising dithianes or imines as directing groups. Chapter 1 introduces the calyciphylline A-type Daphniphyllum alkaloids, their biosynthetic origin and himalensine A as one family member. Current published syntheses of these alkaloids are also highlighted as well as previous work conducted on this project. Chapter 2 focuses on the route development towards the ABCD tetracyclic core. Optimisation of the key enantioselective organocatalytic IMDAF cascade enabled the synthesis of large quantities of the tricyclic core. After elaboration to a key cycloisomerisation precursor, a reductive radical cascade was developed to close the B ring. Finally, a highly diastereoselective low-pressure hydrogenation delivered the completed tetracyclic core. Chapter 3 describes the route from the tetracyclic core through the end-game to access himalensine A. A pyridine and molecular oxygen mediated elimination/C-H oxidation was developed to access an enedione intermediate with the correct oxidation level and chemical handle required to complete the final ring. The E ring was furnished via a Stetter cyclisation and final chemoselective lactam reduction delivered the natural product. Chapter 4 summarises C-H functionalisation within the context of C-N bond forming reactions. A focus is placed on rhodium, it’s ability for directed C-H amination/amidation chemistry and previous work in the field. The challenge of RhIII catalysed C(sp3)-H functionalisation is introduced. Chapter 5 features the development of a novel Cp*RhIII catalysed dithiane-directed amidation of unactivated C(sp3)-H bonds utilising dioxazolone amidating reagents. With the optimised method, a wide range of dioxazolone reagents as well as dithiane partners are well-tolerated. Downstream derivatisation of the amidated products is also demonstrated, including the Corey-Seebach umpolung reaction. Chapter 6 highlights use of a transient imine directing group strategy for metal catalysed C-H functionalisation, and development of this strategy for a Cp*RhIII-catalysed transient imine-directed amidation of unactivated C(sp3)-H bonds using dioxazolone reagents. Completed optimisation studies enable amidation of a sterically hindered aldehyde in good yield, delivering a synthetically useful 1,3 amidoaldehyde derivative.